Critical Thinking Skills and Self-Regulated Learning Of Students during the Covid-19 Pandemic - Linda lidiawati; Indarini Dwi Pursitasari; Leny Heliawati (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
This study aims to analyze critical thinking skills and self-regulated learning of Junior High School Students on Change States of Matter material during online learning during Pandemic Covid 19. The research subjects were 200 junior high school students in the city and district of Bogor who had received the material for Change States of Matter. Data were collected using a test of critical thinking skills with multiple choice types and a questionnaire to measure students' self-regulated learning. The indicators used to measure critical thinking skills refer to FRISCO (Focus. Reason, Inference, Situation, Clarity, Overview), and indicators of learning independence include 3 phases, namely, planning, implementation, and evaluation. The data obtained were then analyzed descriptively and quantitatively. The results of this study indicate that the average level of students' critical thinking skills is still low, namely 33.34%, and the level of learning independence is quite good at 52.45%. There is a significant relationship between students' self-regulated learning and critical thinking skills (Sig = 0.000) in online learning mode.